Does the Embodied Cognition Paradigm Have Implications for Learning? - Anna Re (Scientia Publica Media, 2025)
Cartesian dualism, distinguishing mind from body, has significantly shaped our understanding of cognitive functions, often leading to the perception that these processes exist independently of our physical and bodily experiences. This rigid division has also influenced our approach to educational practices, which tend to be based on a theoretical understanding of cognition. However, emerging theories of embodied cognition are challenging this view by highlighting the fundamental connection between cognitive processes and bodily experiences as well as our physical interactions with the environment. These theories are increasingly supported by neuroscientific research, which recognizes the body as a crucial component of the learning process. Indeed, numerous studies indicate that incorporating bodily experiences into educational settings not only enhances learning, but also makes it more meaningful. When students participate in activities that involve movement and direct engagement with their surroundings, their ability to process and retain information improves, enabling them to translate abstract concepts into tangible forms and internalize them more effectively. This article aims to support a shift in our understanding of cognition away from the rigid dualistic paradigm toward a more holistic perspective of the educational process.